Recent advances in animal nutrition, 1990 - Haresign, William; Cole, D. J. A. (Studies in the agricultural and food sciences., 1990)
Recent Advances in Animal Nutrition 1990 focuses on technologies and controls needed to ensure meat quality. The book first discusses allergic responses to diets in humans. Changes in meat consumption and consumer attitudes; improving the quality of meat; and implications for the future are described. The text looks at legislation and its effect on the feed compounder, including marketing of feeds, medicated feeds, bovine spongiform encephalopathy (BSE), and safety regulations. The book also underscores the control of feed-born bacterial and viral pathogens in farm animals. Animal infections a.